2019
DOI: 10.1093/mnras/stz1271
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of giant molecular clouds and formation of bound star clusters under the influence of momentum stellar feedback

Abstract: Energetic feedback from star clusters plays a pivotal role in shaping the dynamical evolution of giant molecular clouds (GMCs). To study the effects of stellar feedback on the star formation efficiency of the clouds and the dynamical response of embedded star clusters, we perform a suite of isolated GMC simulations with star formation and momentum feedback subgrid models using the moving-mesh hydrodynamics code AREPO. The properties of our simulated GMCs span a wide range of initial mass, radius, and velocity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 113 publications
18
70
0
Order By: Relevance
“…1 of Grudić et al 2019a for a literature compilation of theoretical predictions). For typical local GMCs, these mechanisms (given standard stellar evolution tracks) are more than sufficient to disrupt clouds after a few percent of the total mass is turned into stars (Grudić et al 2016;Kim et al 2018;Li et al 2019). This process must also affect the IMF, as it abruptly cuts off the gas supply for accretion, and could also potentially stir turbulence on small scales.…”
Section: The Necessity Of Feedback Regulationmentioning
confidence: 99%
“…1 of Grudić et al 2019a for a literature compilation of theoretical predictions). For typical local GMCs, these mechanisms (given standard stellar evolution tracks) are more than sufficient to disrupt clouds after a few percent of the total mass is turned into stars (Grudić et al 2016;Kim et al 2018;Li et al 2019). This process must also affect the IMF, as it abruptly cuts off the gas supply for accretion, and could also potentially stir turbulence on small scales.…”
Section: The Necessity Of Feedback Regulationmentioning
confidence: 99%
“…Krumholz & McKee 2005;Blitz & Rosolowsky 2006;Federrath & Klessen 2012), and the impact of stellar feedback (e.g. Grudić et al 2018;Kim et al 2018;Fujimoto et al 2019;Li et al 2019;Keller et al 2020). This is particularly important, because ISM pressures observed at the peak of the cosmic star formation history are several orders of magnitude higher than those observed in disc galaxies today (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that F * ∝ 2 Σcl Mcl, and there is scatter and systematic variation in Σcl and . In observations, numerical simulations, and simple analytic feedback-regulated models (Fall et al 2010;Grudić et al 2018bGrudić et al , 2019Li et al 2019;Wong et al 2019), ∼ (1 + 2000 M pc −2 /Σcl) −1 is generally found ( ∝ Σcl up to a saturation level at ∼ 1), which gives F * ∝ Σ 3 cl Mcl ∝ R 2 cl Σ 4 cl , a highly super-linear dependence. In contrast, the naive assumption that F * ∼ Lcl/R 2 cl (ignoring the fact that star formation is correlated, so assuming stars are uniformly distributed in volume in a cloud) would give F * ∝ Σcl ∝ Σ 2 cl .…”
Section: Dependence On Galactic Environmentmentioning
confidence: 97%